From orality to writing: pantanal reflections - Rondon, Maria Paulina Garcia (Seven Editora, 2023)
This work presents some reflections on the teaching of the Portuguese Language based on the theory of Sociolinguistics, in the process of interaction, and diversity, aimed at combating linguistic prejudice when it comes to linguistic variation in public elementary schools in border regions of MS: Porto Murtinho and Corumbá. The border school community, Paraguay, and Bolivia students find it very difficult to enter a new space of enunciation in which a new language is present: the Portuguese language, spoken and taught in schools in Brazil. Dialects are present in the daily life of these immigrant students and to ignore this fact is a prejudiced action and makes them invisible in an inclusive environment. It also reflects the historical, social, and linguistic aspects that are part of the identification process of the Brazilian and immigrant subjects. The study of the PCNs was also the basis of a support tool for the research and planning of the educational practice. This text represents the analysis of the written production of three border students from Paraguay and Bolivia. It seeks to highlight, in one of the texts, the marks of Portuguese/Spanish bilingualism and, in the other, the marks of Portuguese/Spanish/Guarani multilingualism. The analyses performed reveal the existence of linguistic conflicts manifested in the register of the learners' psychological and cognitive processes when using the linguistic codes and mixing them. Theoretical considerations about interference/transference and linguistic inferences served as support for the analysis of the texts produced by the students. DOI: https://doi.org/10.56238/devopinterscie-094